Pengaruh Kualitas Pelayanan Petugas Aviation Security (AVSEC) terhadap Kepuasan Penumpang Disabilitas di Bandar Udara Adi Soemarmo Solo - Bartholomeus Didan Alfito; Kifni Yudianto (MES Bogor, 2024)
In supporting the security and safety of flights at an airport, there are several requirements that must be met by airport managers. First, reliable human resources in terms of security and comfort. In this case, all aviation security personnel or commonly called Aviation Security (AVSEC). This research aims to determine the influence of the service quality of Aviation Security officers (AVSEC) on the satisfaction of disabled passengers at Adi Soemarmo Airport, Solo. This research uses quantitative methods. The respondents in this study were 67 disabled passengers at Adi Soemarmo Airport, Solo. Data was obtained through distributing questionnaires offline. Data analysis techniques use Simple Linear Regression Test, T Test, Coefficient of Determination Test, and Descriptive Test. The results of this research show that there is an influence of the service quality of Aviation Security officers (AVSEC) on the satisfaction of disabled passengers at Adi Soemarmo Airport, Solo. It is proven from the results of the T Test (Partial) that the T count is 4.748 with a significance value of 0.01 < 0.05. This states that the service quality variable partially influences the passenger satisfaction variable. The results of the Coefficient of Determination Test showed a result of 25.8%, which means that service quality influences passenger satisfaction, while the remaining 74.2% is influenced by other factors that were not studied.